2011
DOI: 10.1177/1538192710382040
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Luz: A Case Study of Gendered Tensions of Romance and Domesticity in the Life of a Former Migrant, Chicana College Student

Abstract: This paper is a case study of a Chicana former migrant in her first year of college through CAMP (College Assistance Migrant Program), and how she negotiated the challenges of family, romance, and the desire to reach her goals. Through narrative analysis, the authors examine the thoughts, words, and experiences of Luz’s life to provide insight to the complex world of vacillating identities across cultural borders and gender role expectations of community, school, and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To help guide the researchers in organizing their analysis, some of the research reviewed previously was used in the template. However, other studies with significant findings, such as those carried out by Reyes et al (2011), Willison and Jang (2009), and Araujo (2011), were also used to analyze the content. This template is to be found in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To help guide the researchers in organizing their analysis, some of the research reviewed previously was used in the template. However, other studies with significant findings, such as those carried out by Reyes et al (2011), Willison and Jang (2009), and Araujo (2011), were also used to analyze the content. This template is to be found in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
“…Another barrier is the unclear expectations of what a college environment will be (Arana et al, 2011). A case study by Reyes, Valles, and Salinas (2011) discusses the difficulty in navigating two different cultures. In summary, many of these factors may contribute to the potential failure for farmworker students in completion of a bachelor’s degree.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…As noted in a study by McHatton, Zalaquett, and Cranson-Gingras (2006), many migrant students reported that barriers to their success included study deficiencies, peer pressure to take part in non-learning activities, dysfunction in the school setting, and work and family matters that interfered with school. In addition, many families simply expect their children to continue the cycle of migrant work and exert substantial pressure on children to perpetuate that cycle (Reyes, Valles, & Salinas, 2011).…”
Section: The Importance Of the Problemmentioning
confidence: 99%